PENGUKURAN KINERJA LINI FANNET DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS DI PT TRIPACIFIC ELECTRINDO (Universitas Esa Unggul, 2018)
AbstractPT. TripacificElektrindo is a manufacturing industry that produces fan electronic devices with quite a large target and target. The emergence of various problems with six big losses in the production process is due to the age of the machines at PT. TripacificElectrindo is old and the maintenance is not optimal so that productivity is low. To solve the problems that occur, companies need to measure performance and analyze machines using the OEE (Overall Equipment Effectiveness) method and cause and effect diagrams.Based on the discussion and analysis, the low value of OEE is reduce speed losses and idle & minor stoppage. Reduce speed losses occur because the machine is old. Idle & minor stoppage occurs due to waiting for material. The occurrence is reduce speed losses and idle & minor stoppage. Reduce speed losses because the performance of the solar engine is less than optimal. To solve the problem, it is necessary to make improvements and changes based on the OEE value of the solar engine so that the fannet line can produce optimally Keywords : TPM (total productive maintenance), OEE (overall equipment effectiveness), six big losses AbstrakPT. Tripacific Elektrindo merupakan salah satu industri manufaktur yang memproduksi alat – alat elekronik kipas angin dengan sasaran dan target yang cukup besar. Timbulnya berbagai permasalahansix big losses pada proses produksinya dikarenakan umur mesin di PT. Tripacific Electrindo yang sudah tua dan perawatan yang dilakukan kurang optimal sehingga produktivitas menjadi rendah. Untuk mengatasi masalah yang terjadi, perusahaan perlu mengukur kinerja dan menganalisa mesin dengan metode OEE (Overall Equipment Effectiveness) dan cause and effect diagram. Berdasarkan pembahasan dan analisa rendahnya nilai OEE adalah reduce speed losses dan idle & minor stoppage. Reduce speed losses terjadi karena umur mesin yang sudah tua. Idle & minor stoppage terjadi karena menunggu material. Terjadinya adalah reduce speed losses dan idle & minor stoppage. Reduce speed losses karena kinerja mesin matahari kurangoptimal. Untuk mengatasi masalah, maka perlu dilakukan perbaikan dan perubahan berdasarkan nilai OEE pada mesin matahari sehingga lini fannet dapat berproduksi dengan optimal. Kata kunci : TPM (total productive maintenance), OEE (overall equipment effectiveness), six big lossesin-top:0cm;margin-right:36.0pt;margin-bottom: 0cm;margin-left:36.0pt;margin-bottom:.0001pt;text-align:justify;line-height: normal'>Kata kunci: produktivitas, TPM, overall equipment effectiveness